A Unique Case of Relapsing Polychondritis Presenting with Acute Pericarditis - John V. Higgins; Uma Thanarajasingam; Thomas G. Osborn (Case Reports in Rheumatology)
Relapsing polychondritis (RP) is an inflammatory disease of the cartilaginous tissue primarily affecting the cartilaginous structures of the ear, nose, joints, and the respiratory system. Cardiovascular complications of RP are associated with high morbidity and mortality and occur most commonly as valvular disease. Pericarditis is a less common complication, occurring in 4% of patients with RP and has not previously been described at presentation. We describe a case of relapsing polychondritis with acute pericarditis at presentation.